Kajian Perkembangan Sistem Saraf Pusat pada Mus musculus - Yafitriani Loi; Nailla Ramadani; Cinta Serlina; Bunga Deli Anjani; Jodion Siburian; Afreni Hamidah; Desfaur Natalia (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
The development of the central nervous system in Mus musculus is a complex biological process that occurs through several stages, including neurulation, neuronal proliferation, neuronal migration, neuronal differentiation, neurogenesis, and synaptogenesis. This study aimed to explore the stages of central nervous system development in Mus musculus and the factors influencing them through a literature review approach. The method used was descriptive qualitative analysis based on scientific journals and books published between 20162026. The results showed that neurulation plays a role in forming the basic structure of the brain and spinal cord, while the stages of proliferation, migration, differentiation, and synaptogenesis contribute to the formation of neural networks and nervous system function. This process is influenced by genetic and environmental factors, including nutrition, hormones, stress, and exposure to chemical substances. The use of Mus musculus as an animal model has significantly contributed to the development of neurobiology and neurological health research.